Three essays on information intermediaries in the financial market - Dong, Yi (2012)
This dissertation includes three essays. The first essay investigates the relation between a firm‟s visibility in blog spaces, termed blog exposure, and the cross-sectional stock returns. I show that blog exposure is fundamentally different from the traditional media coverage, and securities with low blog exposure earn higher returns than stocks with high blog exposure. Contrary to traditional media coverage, the return premium associated with blog exposure cannot be explained by either the illiquidity hypothesis or the investor recognition hypothesis based on rational agent framework. Instead, the results suggest that blog effect can be attributed to the limited attention theory and cannot be arbitraged due to investors‟ self attribution and short-sales constraints. I document the blog based abnormal return is due to mis-pricing which will reverse later, not compensation for risk factor. This work points out the importance of blogs in information dissemination, especially for the stocks with limited attention.